TRANSFORMASI KEPEMIMPINAN SEKOLAH DASAR: STRATEGI EFEKTIF MENUJU PENDIDIKAN ABAD 21 - Timtim Siti Mariam; Yeni Yuniarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research discusses the leadership strategies of school principals in developing human resources in elementary schools in the 21 st century era. The aim is to identify effective strategies, reveal the challenges faced, and evaluate their impact on curriculum implementation and improving the quality of education. This research highlights the importance of transformational and distributed leadership approaches to support innovation and collaboration. This research uses a qualitative approach with a case study design. Data was collected through in-depth interviews, direct observation and document analysis. Purposive sampling technique was used to select 15 relevant informants. Data were analyzed thematically, involving coding, identifying major themes, and interpretation. Validity is maintained through method triangulation, member checking, and peer debriefing. Based on research, school principals in Majalaya District apply various leadership strategies, such as teacher empowerment, collaboration, and transformational approaches. The main challenges include limited funds, time, and teacher resistance. As a result, the majority of teachers are more motivated and actively involved. Implementation of the 21 st century curriculum was carried out in stages with stakeholder collaboration, resulting in increased performance of teachers, staff and learning effectiveness. Research shows that the success of school principal leadership is influenced by unique approaches, challenges and collaboration. SDN Padasuka 05 focuses on continuous training, SDN Kubang on collaboration, SDN Leuwidulang on transformation. Challenges in the form of funds, resistance and time are overcome by increasing teacher motivation. The work culture supports the 21 st century curriculum through collaboration between society and technology.